An Experimental Investigation of Oil Film Temperatures in Elliptical Profile Journal Bearing - Rakesh Sehgal (Japanese Society of Tribologists, 2013)
Hydrodynamic journal bearings experience significant variation in oil film temperature. Reliable data of operating temperatures in these journal bearings are very useful and important for practical bearing designers and mathematical modellers. Here, an elliptical journal bearing has been tested to access the temperature rise at oil-bush interface with three grade oils at loads varying from 100 N to 600 N and speeds = 3000, 3500, 4000 rpm at constant oil supply pressure. The results show that with increase in load at constant speed and pressure, and with increase in speed at constant load and pressure, the oil film temperature increases in the central plane of both the lobes of the bearing for all grade oils under study. Further, it is observed that under the given operating conditions, oil 2 gives the coolest operation of the elliptical bearing under analysis.